2017
DOI: 10.3389/fnmol.2017.00026
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Post-synaptic Density Fractions from Shank3 Mutant Mice Reveals Brain Region Specific Changes Relevant to Autism Spectrum Disorder

Abstract: Disruption of the human SHANK3 gene can cause several neuropsychiatric disease entities including Phelan-McDermid syndrome, autism spectrum disorder (ASD), and intellectual disability. Although, a wide array of neurobiological studies strongly supports a major role for SHANK3 in organizing the post-synaptic protein scaffold, the molecular processes at synapses of individuals harboring SHANK3 mutations are still far from being understood. In this study, we biochemically isolated the post-synaptic density (PSD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 54 publications
(95 reference statements)
5
80
1
Order By: Relevance
“…In previously published models, analysis of anxiety-like behavior measured either elevated mazes, in the open fields or in dark/light emergence boxes have demonstrated a relationship between the targeted isoforms and the manifestations of anxiety like-behavior. While little differences were observed in mouse models with Δ4-9, Δ4-7, Δ9, and Δ11 deletions ( Peça et al, 2011 ; Wang et al, 2011 ; Schmeisser et al, 2012 ; Yang et al, 2012 ; Drapeau et al, 2014 ; Lee et al, 2015 ; Jaramillo et al, 2016 ; Reim et al, 2017 ; Vicidomini et al, 2017 ) increased levels of anxiety were reported in mice with Δ13, Δ13-16, and Δ21 deletions or point mutations ( Peça et al, 2011 ; Kouser et al, 2013 ; Speed et al, 2015 ; Mei et al, 2016 ; Zhou et al, 2016 ; Copping et al, 2017 ; Jaramillo et al, 2017 ). Increased levels of anxiety were confirmed in the light-dark emergence test and in the open field in the Δ4-22 mouse model from Wang et al, 2016b and colleagues and in the elevated maze and in the open field in our model.…”
Section: Discussionmentioning
confidence: 97%
“…In previously published models, analysis of anxiety-like behavior measured either elevated mazes, in the open fields or in dark/light emergence boxes have demonstrated a relationship between the targeted isoforms and the manifestations of anxiety like-behavior. While little differences were observed in mouse models with Δ4-9, Δ4-7, Δ9, and Δ11 deletions ( Peça et al, 2011 ; Wang et al, 2011 ; Schmeisser et al, 2012 ; Yang et al, 2012 ; Drapeau et al, 2014 ; Lee et al, 2015 ; Jaramillo et al, 2016 ; Reim et al, 2017 ; Vicidomini et al, 2017 ) increased levels of anxiety were reported in mice with Δ13, Δ13-16, and Δ21 deletions or point mutations ( Peça et al, 2011 ; Kouser et al, 2013 ; Speed et al, 2015 ; Mei et al, 2016 ; Zhou et al, 2016 ; Copping et al, 2017 ; Jaramillo et al, 2017 ). Increased levels of anxiety were confirmed in the light-dark emergence test and in the open field in the Δ4-22 mouse model from Wang et al, 2016b and colleagues and in the elevated maze and in the open field in our model.…”
Section: Discussionmentioning
confidence: 97%
“…A comprehensive analysis of mTORC1 activity in various brain regions of Shank3 mutant mice, together with the direct measurement of ribosomal quantity (both mRNA and protein) and activity, could provide important clues regarding the detailed mechanisms behind this. In this regard, it is worth noting that in a recent quantitative proteomic analysis of the striatal PSD of Shank3 mutant mice ( Shank3 Δ 11 −/− ), the levels of several ribosomal proteins were increased compared with WT mice ( Reim et al, 2017 ). Shank3 proteins are coupled with metabotropic glutamate receptors (mGluRs) via Homer ( Tu et al, 1999 ) and regulate their synaptic expression and signaling ( Verpelli et al, 2011 ; Vicidomini et al, 2016 ; Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…While many of the genes enriched for D1+ and D2+ expression are not exclusive to the striatum and are more broadly expressed (as demonstrated by the enrichment signal at the lowest specificity threshold), the striatum has been implicated in ID and autism pathology by numerous studies [97][98][99][100][101][102][103][104][105][106] . The striatum is particularly compelling as it has been linked to repetitive behaviors 97 core to the autism phenotype and also to genes known to be involved in DD, including CHD8, SHANK3, FOXP2, and KCNA4 98,99,102,105,106 . While the striatum is most strongly linked to autism core phenotypes, our observation of enrichment in a more general DD cohort suggests that, while the general bias of cortex genes to ID and striatum genes to ASD 101 still holds, the diverse expression patterns of genes across the brain at complex developmental time points may have substantial functional overlap among subtypes of NDDs that will require deep phenotyping and imaging to tease apart.…”
Section: Discussionmentioning
confidence: 99%